An Approach for Numerical Modeling of Gob Compaction Process in Longwall Mining - Yadav A.; Behera B.; Sahoo S.K.; Singh G.S.P.; Sharma S.K. (My University, 2025)
A field representative modeling of the gob behavior is critical for the understanding of the associated mechanics of strata behavior in longwall workings. The findings of theoretical models and laboratory tests on the simulated gob material have shown the strain hardening behavior of the gob material. The double-yield material model, which is a built-in constitutive model in FLAC3D, has significant potential to simulate the gob compaction process as it represents materials which undergo irreversible compaction in addition to shear yielding. Apart from this, several researchers have attempted using modified elastic model or applied nodal force in reaction to the strain in the gob area as per the well-known theoretical relations to meet this requirement. Although these models can simulate the mechanical response of the gob for subcritical and critical extraction widths, they do not apply to super-critical extraction width as the gob stress may exceed the in situ stress level in such cases. For overcoming these limitations, a standard approach has been developed and validated in this paper, which can be used for simulating the gob behavior in super-critical longwall workings as well. The complete study is divided into two stages wherein the laboratory scale compression test on the simulated gob material has been numerically replicated to develop preliminary confidence followed by a parametric study of the double-yield constitutive parameters for a rational estimation of their values in different conditions. The calibrated model has been used for verifying its results by plane strain modeling of two different longwall workings, using well-established empirical and analytical findings and field observations. The approach suggested in this study can be used for the efficient modeling of the gob behavior of longwall panels under varying geo-mining conditions without compromising the accuracy of the numerical model. The meticulously validated model can be helpful in rational estimation of stress redistributions around the gob area apart from load transfer on the barrier pillar. © 2020, Society for Mining, Metallurgy & Exploration Inc.